META-ANALYSIS OF THE EFFECT OF INQUIRY TRAINING LEARNING MODEL ON THE LEARNING OUTCOMES OF HIGH SCHOOL PHYSICS STUDENTS CLASS X - Rahmadhani, Rahmadhani (Journal of Learning and Technology in Physics, 2024)
Learning physics is considered difficult and unpleasant by most students. This is because at the time of learning the teacher did not apply a learning model that involved students, resulting in low student learning outcomes. This study aims to reanalyze the influence of the inquiry training learning model on the learning outcomes of high school physics students in class X. This type of research is a quantitative metaanalysis. The sample consists of 10 articles with S1-S6 reputation. The collection of articles uses an instrument, namely an observation sheet. The results obtained that the average effect size of the influence of inquiry training learning model on physics learning outcomes in high school class X is 0.885 in the medium category and the inquiry training learning model is effectively used on heat material with an effect size of 1.162 in the high category. Based on the results of this study, it was found that there was an influence of the inquiry training learning model on the learning outcomes of high school physics students in class X.Keywords: Inquiry Training; Learning Outcomed